Single and combined effects of dimethoate and malathion on oxidative stress biomarkers in the non-target freshwater mussel Dreissena polymorpha - Serdar Osman; Yildirim Numan; Yildirim Nuran Cikcikoglu (Oceanological and Hydrobiological Studies)
This study evaluates the single and combined effects of dimethoate (DI) and malathion (MA) on oxidative stress biomarkers in the freshwater mussel Dreissena polymorpha, estimating the potential harm of these pesticides on aquatic ecosystems. Superoxide dismutase (SOD) and catalase (CAT) activities, and glutathione (GSH) and lipid peroxidation (TBARS) levels were determined in D. polymorpha exposed to sublethal concentrations of DI, MA and a combination of the two during 24 and 96 h periods. The results showed that the GSH levels were decreased but the TBARS levels were increased in all the exposure groups after 24 and 96 h compared to the control. It was observed that SOD activity decreased but CAT activity increased in all the DI exposure groups after 24 h compared to the control. At the end of 96 hours, it was observed that CAT and SOD activities increased again in some exposure groups compared to the control. Exposure time also had an effect on biomarkers in different levels. According to the results, the cytotoxicity of DI and MA combination depended on their concentrations. DI or/ and MA, in sub-lethal concentrations, induced oxidative damages in D. polymorpha. Combined exposure of the pesticides can alter their toxicity and may be evidence of increased toxicity and oxidative stress.